Pengaruh Minat Belajar Terhadap Hasil Belajar Matematika Siswa Kelas VI SD Negeri 056/VII Sungai Baung Tahun Ajaran 2025/2026 - Pebri Ningsih, Eki; Yani, Andri; Hardani; Nurmala Sari, Sindi; Tania, Elsi; Ferinaldi; Agustandi, Egi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the uncertainty that students who have high learning interest do not necessarily achieve high learning outcomes, and vice versa. The purpose of this research is to describe the influence of learning interest on learning outcomes. This research uses a quantitative approach with a correlational method. The sampling technique used is total sampling technique, so the sample in this study amounts to 16 respondents. The research was conducted using a questionnaire instrument and midterm mathematics exam scores, with the number of questionnaire statements being 38 items. Based on the analysis, the data are normally distributed and linearly patterned. The data analysis technique used to test the hypothesis is product moment correlation, for the significance test using the t-test, followed by the coefficient of determination formula to state the magnitude of the influence of variable X on Y. Based on the results of data analysis, it shows that rcount > rtable or 0.816 > 0.497, so Ha is accepted. Based on the calculation of the coefficient of determination, it was obtained that 66.58% of learning interest influences learning outcomes, while the remaining 33.42% is influenced by other factors. Thus, it can be concluded: There is a significant influence between learning interest and learning outcomes of grade VI students of SD Negeri 056/VII Sungai Baung Academic Year 2025/2026.